Pengaruh Budaya Organisasi, Komitmen Organisasional, Dan Motivasi Ekstrinsik Terhadap Citizenship Behavior Pegawai Kantor Kapanewon Depok - Kurniawati, Maria Jeanice; Kurniawan, Ignatius Soni (J-MAS (Jurnal Manajemen dan Sains), 2024)
This research aims to examine the influence of organizational culture, organizational commitment and extrinsic motivation on the citizenship behavior of Depok District Office Employees. This study was a quantitative study and primary data were taken using a questionnaire with 32 respondents. Sampling techniques using the saturated sample method. The data is collected through direct surveys and then processed using multiple linear regression analysis. The results showed that organizational culture, organizationa